PENGARUH BEBAN KERJA DAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PADA PT CAKRA RAYA TEKNOLOGI TANGERANG - Sulkan Saputra; Maghfiroh Yanuarti (Jurnal Menara, 2026)
The purpose of this study is to know the effect of workload and occupational safety and health (K3) on employee performance at PT Cakra Raya Teknologi, Tangerang, both partially and simultaneously. The problem underlying this research is the decline in employee performance, as indicated by low target achievement, high workload and inadequate occupational safety and health K3. This study uses an quantitative method with a saturated sampling technique, involving 51 respondents. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results showed that workload has a significant effect on employee performance, with a t-value of 7.380 and significance value of 0,05. In addition, occupational safety and health (K3) is also proven to have a significant effect on employee performance, with a t-value of 6.316 and significance value of 0,05. Simultaneously, workload and occupational safety and health (K3) have a significant effect on employee performance, with a F-value of 41.856 > F table 2.790 and a significance value of 0,05. The determination coefficient indicates that workload contributes 52,1% to employee performance, while occupational safety and health K3 contributes 44,4% to employee performance, simultaneously, both variables contribute 63,1% to employee performance, while the remaining percentage is influenced by other factors outside this study